The village by the sea - Desai, Anita. 1937- (Haryana : Penguin Random House India, 1984)
When their family falls on hard times, thirteen-year-old Lila and her twelve-year-old brother, Hari, try desperately to keep their home intact--an almost impossible task until Hari gets a chance to go to Bombay and returns with some positive plans for the future.
Originally published: London : Heinemann, 1982.
DELL
Keywords: Family life -- Fiction -- India; Brothers and sisters -- Fiction; Poverty -- Fiction; Family problems -- Fiction; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Social Issues / Homelessness & Poverty; JUVENILE FICTION / People & Places / Asia; India -- Fiction -- Social life and customs